Collective behaviour of climate indices in the North Pacific air-sea system and its potential relationships with decadal climate changes - 王晓娟 支蓉 何文平 龚志强 (Chinese physics B, 2012)
A climate network of six climate indices of the North Pacific air-sea system is constructed during the period of 1948-2009. In order to find out the inherent relationship between the intrinsic mechanism of climate index network and the important climate shift, the synchronization behaviour and the coupling behaviour of these indices are investigated. Results indicate that climate network synchronization happened around the beginning of the 1960s, in the middle of the 1970s and at the beginnings of the 1990s and the 2000s separately. These synchronization states were always followed by the decrease of the coupling coefficient. Each synchronization of the network was well associated with the abrupt phase or trend changes of annually accumulated abnormal values of North Pacific sea-surface temperature and 500-hPa height, among which the one that happened in the middle of the 1970s is the most noticeable climate shift. We can also obtain this mysterious shift from the first mode of the empirical orthogonal function of six indices. That is to say, abrupt climate shift in North Pacific air-sea system is not only shown by the phase or trend changes of climate indices, but also might be indicated by the synchronizing and the coupling of climate indices. Furthermore, at the turning point of 1975, there are also abrupt correlation changes in the yearly mode of spatial degree distribution of the sea surface temperature and 500-hPa height in the region of the North Pacific, which further proves the probability of climate index synchronization and coupling shift in air sea systems.